Optimization of Social Media Management in Enhancing the Brand Image of Islamic Boarding Schools - Hefniy, Hefniy; Munawaroh, Madinatul; Habsi, Malikul (Journal of Educational Management Research, 2025)
This study investigates the role of social media optimization in enhancing the brand image of Islamic boarding schools (pesantren). With the rapid growth of digital communication, social media has become a critical tool for educational institutions to engage with their audience and improve their public perceptionSocial media plays a vital role in brand identity creation, with professional social media management, structured content strategies, and platform-specific engagement being key factors in achieving successful branding. Using a multi site approach, the study combined observational data and interviews with social media admins from two pesantren, PP. Al-Mashduqiah and PP. Asy-Syarify. The findings revealed that professional social media admins significantly contribute to maintaining a positive public image, that a structured content strategy is crucial for consistent engagement, and that different platforms are more effective for targeting specific audience segments. This research contributes to the understanding of how religious institutions can leverage social media for branding, particularly in a competitive educational landscape. Recommendations include investing in professional social media management, adopting structured content planning, and tailoring content to specific platforms for optimal reach.